Functional Connectivity Disruption in Frail Older Adults Without Global Cognitive Deficits - Suárez-Méndez, Isabel; Doval, Sandra; Walter, Stefan; Pasquín, Natalia; Bernabé, Raquel; Gallo, Ernesto Castillo; Valdés, Myriam; Maestú, Fernando; López-Sanz, David; Rodríguez-Mañas, Leocadio (Frontiers in Medicine, 2020)
Frailty is a common representation of cumulative age-related decline that may precede disability in older adults. In our study, we used magnetoencephalography (MEG) to explore the existence of abnormalities in the synchronization patterns of frail individuals without global cognitive impairment. 54 older (≥ 70 years) and cognitively healthy (Mini-Mental State Examination ≥ 24) adults, 34 robust (not a single positive Fried criterion), and 20 frail (≥ 3 positive Fried criteria) underwent a resting-state MEG recording and a T1-weighted magnetic resonance imaging scan. Seed-based functional connectivity (FC) analyses were used to explore group differences in the synchronization of fronto-parietal areas relevant to motor function. Additionally, we performed group comparisons of intra-network FC for key resting-state networks such as the sensorimotor, fronto-parietal, default mode, and attentional (dorsal and ventral) networks. Frail participants exhibited reduced FC between posterior regions of the parietal cortex (bilateral supramarginal gyrus, right superior parietal lobe, and right angular gyrus) and widespread clusters spanning mainly fronto-parietal regions. Frail participants also demonstrated reduced intra-network FC within the fronto-parietal, ventral attentional, and posterior default mode networks. All the FC results concerned the upper beta band, a frequency range classically linked to motor function. Overall, our findings reveal the existence of abnormalities in the synchronization patterns of frail individuals within central structures important for accurate motor control. This study suggests that alterations in brain connectivity might contribute to some motor impairments associated with frailty.